Thermo-mechanical characterization of electrospun polyurethane/carbon-nanotubes nanofibers: a comparative study - A. Shaker; Amira T. Khedewy; Mohamed A. Hassan; Marwa A. Abd El-Baky (Scientific Reports, 2023)
Abstract Creating ultrathin, mountable fibers from a wide range of polymeric functional materials has made electrospinning an adequate approach to producing highly flexible and elastic materials. In this paper, electrospinning was utilized to produce thermoplastic polyurethane (TPU) nanofibrous membranes for the purpose of studying their thermal and mechanical properties. Towards a study of the effects of fiber orientation and multi-walled carbon nanotubes (MWCNTs) as a filler on both mechanical and thermal characteristics of electrospun TPU mats, an experimental comparison was held between unidirectional and randomly aligned TPU and TPU/MWCNTs nanofibrous structures. The incorporation of MWCNTs into randomly oriented TPU nanofibers resulted in a significant increase in Young's modulus (E), from 3.9 to 7.5 MPa. On the other hand, for unidirectionally spun fibers, Young's modulus increased from 17.1 to 18.4 MPa upon the addition of MWCNTs. However, dynamic mechanical analysis revealed a different behavior. The randomly oriented specimens exhibited a storage modulus with a significant increase from 180 to 614 MPa for TPU and TPU/MWCNTs mats, respectively, and a slight increase from 119 to 143 MPa for unidirectional TPU and TPU/MWCNTs mats, respectively. Meanwhile, the loss modulus increased with the addition of MWCNTs from 15.7 to 58.9 MPa and from 6.4 to 12 MPa for the random and aligned fibers, respectively. The glass transition values for all the mats fell in the temperature range of – 60 to − 20 °C. The thermal degradation of the membranes was not significantly affected by the addition of MWCNTs, indicating that the mixing of the two constituents did not change the TPU’s polymer structure and that the TPU/MWCNTs nanocomposite exhibited stable thermal degradation properties.